MEKANISME PERTAHANAN DIRI PENDERITA BIPOLAR DISORDER - As’ad; Moh. Hafid (Konseling At-Tawazun, 2023)
Self defense mechanism is an internal drive process that protects an individual from anxiety and problems. While Bipolar disorder (bipolar disorder) is a condition in which a person experiences a psychological disorder with indications of extreme mood and emotional changes. This study aims to describe what things are done by a teenager diagnosed with bipolar disorder as a self defense mechanism. This study uses a descriptive qualitative approach. The data in this research is the result of in depth interview conducted by researchers with research subjects who agree to keep their real identities secret. The research is located in Batu City East Java. The results showed that the research subjects did at least four things as a defense mechanism, namely sublimation, displacement, rationalization, and regression.